On the Hyers-Ulam Stability of First-Order Impulsive Delay Differential Equations. (22nd March 2016) - Zada, Akbar; Faisal, Shah; Li, Yongjin
Abstract : This paper proves the Hyers-Ulam stability and the Hyers-Ulam-Rassias stability of nonlinear first-order ordinary differential equation with single constant delay and finite impulses on a compact interval. Our approach uses abstract Gronwall lemma together with integral inequality of Gronwall type for piecewise continuous functions.